Long-Term Outcomes Following Hepatic Resection and Radiofrequency Ablation of Colorectal Liver Metastases. (1st February 2010) - McKay, Andrew; Fradette, Katherine; Lipschitz, Jeremy
Abstract : Recently some have called for randomized controlled trials comparing RFA to hepatic resection, particularly for patients with only a few small metastases. The objectives were to compare local recurrence and survival following RFA and hepatic resection for colorectal liver metastases. This was a retrospective review of open RFA and hepatic resection for colorectal liver metastases between January 1998 and May 2007. All patients who had RFA were considered to have unresectable disease. 58 patients had hepatic resection and 43 had RFA. A 5-year survival after resection was 43% compared to 23% after RFA. For patients with solitary lesions, a 5-year survival was 48% after resection and 15% after RFA. Sixty percent of patients suffered local recurrences after RFA compared to 7% after hepatic resection. RFA is inferior to resection. The results observed in this study support the consensus that RFA cannot be considered an equivalent procedure to hepatic resection.